2019
DOI: 10.1177/0145561319860527
|View full text |Cite
|
Sign up to set email alerts
|

Management of Upper Airway Leech Infestations

Abstract: Purpose: Upper airway foreign body is one of the most encountered clinical situations in otolaryngology practice. In rare conditions, a living organism may be a foreign body in the upper airway. In this study, we demonstrate 19 patients with leech infestations in nose, nasopharynx, and larynx. Methods: This study was enrolled with 19 patients between 2012 and 2016 in a regional state hospital. All of the patients were admitted to clinic with these complaints: epistaxis, hemoptysis, coughing, foreign body sensa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 8 publications
3
15
0
Order By: Relevance
“…Our patient presented with unexplained recurrent intermittent bleeding from the nose or throat, foreign body sensation and with a recent history of drinking or swimming in unsafe water. This clinical presentation is similar to cases reported especially in the at-risk groups like children, 3 , 6–9 elderly, 13 , 14 , 20 and mentally challenged persons. 12 Of the 19 cases reported in his series, Harun 3 found 15 children, with 10 being under 10 years of age, a range in which our patient lies.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Our patient presented with unexplained recurrent intermittent bleeding from the nose or throat, foreign body sensation and with a recent history of drinking or swimming in unsafe water. This clinical presentation is similar to cases reported especially in the at-risk groups like children, 3 , 6–9 elderly, 13 , 14 , 20 and mentally challenged persons. 12 Of the 19 cases reported in his series, Harun 3 found 15 children, with 10 being under 10 years of age, a range in which our patient lies.…”
Section: Discussionsupporting
confidence: 88%
“…This clinical presentation is similar to cases reported especially in the at-risk groups like children, 3 , 6–9 elderly, 13 , 14 , 20 and mentally challenged persons. 12 Of the 19 cases reported in his series, Harun 3 found 15 children, with 10 being under 10 years of age, a range in which our patient lies. The youngest reported case of leech infestation is of a 9-month-old child.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The most common clinical feature of leech parasites is nasal infestation and recurrent unexplained epistaxis (8). In a 19-patient study conducted between 2012 and 2016, it was shown that all patients (12 nasal, 6 nasopharynx, 1larynx) presented with at least one of the following findings: epistaxis, hemoptysis, coughing, foreign body sensation at the site, and bloody stool (9). In our case, hemoptysis and shortness of breath due to leech attachment to the oropharyngeal region and mild anemia were observed.…”
Section: Discussionmentioning
confidence: 99%